2021
DOI: 10.3389/fphys.2021.691633
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Whole-Organism Metabolic Rate From Red Blood Cells in Birds

Abstract: Metabolic rate is a key ecological variable that quantifies the energy expenditure needed to fuel almost all biological processes in an organism. Metabolic rates are typically measured at the whole-organism level (woMR) with protocols that can elicit stress responses due to handling and confinement, potentially biasing resulting data. Improved, non-stressful methodology would be especially valuable for measures of field metabolic rate, which quantifies the energy expenditure of free-living individuals. Recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 63 publications
2
28
0
Order By: Relevance
“…In our study, temperatures at capture ranged between ∼4-27°C (Figure S1). Assuming that the thermoneutral zone of our great tit population is between 15°C and 30°C (Broggi et al, 2005; Malkoc, Casagrande, et al, 2021), we collected two thirds of the baseline and stress-induced corticosterone samples at temperatures below the great tits’ thermoneutrality. The thermoneutral zone is typically determined in a laboratory situation and only insufficiently reflects thermoregulatory challenges and processes that animals face under natural conditions (e.g., Mitchell et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, temperatures at capture ranged between ∼4-27°C (Figure S1). Assuming that the thermoneutral zone of our great tit population is between 15°C and 30°C (Broggi et al, 2005; Malkoc, Casagrande, et al, 2021), we collected two thirds of the baseline and stress-induced corticosterone samples at temperatures below the great tits’ thermoneutrality. The thermoneutral zone is typically determined in a laboratory situation and only insufficiently reflects thermoregulatory challenges and processes that animals face under natural conditions (e.g., Mitchell et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals can differ in how strongly they respond to variation in ambient temperature, for instance in metabolic rate (Briga & Verhulst, 2017; Careau et al, 2014; Kar et al, 2021), foraging activity (Hall & Chalfoun, 2019), or incubation behavior (Cones et al, 2021). Since glucocorticoids support the regulation of such traits (Romero & Wingfield, 2016), quantifying the extent of glucocorticoid plasticity within and among individuals of wild vertebrate populations is crucial for evaluating the potential of these mechanisms to evolve (e.g., Angelier & Wingfield, 2013; Guindre-Parker, 2020; Hau et al, 2016; Malkoc, Mentesana, et al, 2021; Taff & Vitousek, 2016; Wada & Sewall, 2014). Individual differences are the raw material of selection, and for evolution to occur these individual differences have to harbor a heritable component.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the observed relationship between BMR and COX in RBCs could reflect a synergistic response to maintain vascular and respiratory homeostasis, either because the blood cells contribute to blood flow regulating vascular tone, and/or that they are influenced by the same regulatory pathways that reflect the requirements of other energy demanding tissues (e.g., liver). Malkoc et al (2021) reported that oxygen consumption at the cellular level in RBCs of great tits (Parus major) is directly related to oxygen consumption at the organismal level. This pattern was observed only when birds did not display signs of stress as inferred from plasma corticosterone concentrations, indicating that work examining the effects of stress on metabolic rate at both the mitochondrial and organismal level warrants further exploration.…”
Section: Changes In Erythrocyte Metabolic Activitymentioning
confidence: 99%